The implementation of ESL curriculum policy and its impact on practice in selected primary schools of Madurai District, India / Latha d/o Ravindran - Ravindran, Latha (2013)
This study is driven by the need to examine the implementation of ESL curriculum policy and its implications for practice. Implementation of the ESL policy is an evolutionary process which is not always linear or predictable. As policy is transformed and adapted to conditions of the implementing unit, effective implementation may have different meanings in different settings. Gaps between policy planning and implementation often exist, despite careful planning of the educational policy. Drawing on a qualitative design, various approaches such as interviews with the key stakeholders, interviews with students, document analysis, field notes and classroom observations helped the researcher to understand the salient features of the policy and its impact on instructional practices. Research question one on policy changes deals with major stakeholders’ views on policy changes and the key concepts adopted by the government in implementing the policy. The second research question is related to the planning and the teaching of the curriculum, understanding of the curriculum and responses to policy changes. Research question three examines how the context of the school affects curriculum implementation. Results of this study have implications for language studies in India as well as in other contexts where language teaching is concerned. Gaps were identified between what is envisioned and what happened in reality and teachers operated under different paradigms and did not totally agree with the policy. The teachers saw their roles differently and adapted parts of the policy. Teachers being passive implementers, a mismatch of intention and execution in policy was identified. Factors that affected implementation mostly related to the context of the school, culture, resource materials, teaching experience, pedagogy, professional development and goals of the policy.